Design and Performance Testing of a Keychain Product Mold for a Learning Module in the Metrology and Plastic Moulding Laboratory at XYZ - Anggit Kristiawan, Timotius; Setiyawan, Trio; Tono Putri, Farika; Ayu Janitra, Atikah; Syukur Alfauzi, Abdul; Mujiarto, Iman; Ningtias, Dieta Wahyu Asry (Jurnal Rekayasa Mesin, 2025)
In the current technological era, plastic assumes a crucial role in daily life. This is substantiated by the continuously escalating demand for plastic-based products. Manufacturing items by reshaping plastic raw materials necessitates the use of plastic forming tools or machinery. A prevalently utilized apparatus is the injection molding machine, which employs a specialized mold. The mold design process mandates rigorous calculations and planning to ensure the production of dimensionally identical and uniform parts, thereby facilitating mass production. The primary objective of this research was to design, implement, and validate a mold for plastic injection molding, specifically intended for the mass production of keychains. The methodology employed was the Sighley's Mechanical Engineering Design approach, which encompasses the following sequential procedures: Problem Identification, Problem Definition, Synthesis, Analysis and Optimization, Evaluation, and Presentation. The fabricated keychain mold yielded two products per injection cycle, with mold dimensions (L×W×H) measuring 110 mm×100 mm×160 mm. The mold was mounted on the injection molding machine, requiring a clamping force of 46710 N, with system control provided by an Arduino and cooling facilitated by an external fan. The test results identified the optimal operating parameters for a single molding process, comprising a heating temperature of 210°C, an injection time of 17 seconds, and a cooling time of 12 seconds.